Pathway infiammatorio del Sistema del Complemento nelle ascidie: sequenziamento e caratterizzazione funzionale del recettore dell’anafilatossina C3a di Ciona intestinalis - Melillo, Daniela; Tota, Bruno; Panno, Maria Luisa; Pinto, Maria Rosaria (My University, 2014)
In mammals, the bioactive fragment C3a, released from C3 during complement activation, is a potent mediator of inflammatory reactions and exerts its functional activity through the specific binding to cell surface G protein-coupled seven-transmembrane receptors. Recently, a C3a-mediated chemotaxis of hemocytes has been demonstrated in the deuterostome invertebrate Ciona intestinalis and an important role for this molecule in inflammatory processes has been suggested. In this study, we have cloned and characterized the CiC3aR molecule involved in the CiC3a-mediated chemotaxis and studied its expression profile. The sequence of CiC3aR, encoding a 95,394 Da seventransmembrane domain protein, shows the highest sequence homology with mammalian C3aRs. Northern blot analysis revealed that the CiC3aR is expressed abundantly in the heart and neural complex and to a lesser extent, in the ovaries, hemocytes, and larvae. Three polyclonal antibodies raised against peptides corresponding to CiC3aR regions of the first and second extracellular loop and of the third intracellular loop, react specifically in Western blotting with a single band of 98-102 kDa in hemocyte protein extracts. Immunostaining performed on circulating hemocytes with the three specific antibodies revealed that CiC3aR is constitutively expressed only in hyaline and granular amoebocytes. In chemotaxis experiments, the antibodies against the first and second extracellular loop inhibited directional migration of hemocytes toward the synthetic peptide reproducing the CiC3a C-terminal sequence, thus providing the compelling evidence that C. intestinalis.expresses a functional C3aR homologous to the mammalian receptor. These findings further elucidate the evolutionary origin of the vertebrate complement-mediated proinflammatory process
Dottorato di Ricerca in Biologia Animale, XIX Ciclo,a.a.2005-2006
Keywords: Biologia animale; Vertebrat